Visual metaphtonymy in automobile femvertising. Issue 1 (2nd January 2022) - Chatti, Sami
Abstract: In a 2017 landmark reform, Saudi authorities decided to lift the ban on women driving in this conservative society. In tribute to women's newly-gained freedom to drive, major automakers turned to Twitter to launch creative femvertising campaigns that vividly articulate the female empowering motto 'driving is feminine'. Building on the eloquence of visual rhetoric, which combines the communicative force of figurative language with the expressive potential of visual imagery, automobile advertisers resorted to visual metaphtonymy to efficiently target prospective female consumers. The selection of this visual compound, which emerges from the intricate interplay between metaphor and metonymy, allows for a dynamic interaction between the highlighting function of metonymy and the mapping role of metaphoric thought to establish informed parallels between femininity and automobility. Analysis of survey data on the likeability, complexity and effectiveness of a representative sample of four digital automobile advertisements asserts the role and value of visual metaphtontonymy in automobile femvertising.